The method of distinction monofractal and multifractal process from time series - Kirichenko, L. (My University, 2014)
Based on the numerical analysis of the sample multifractal characteristics obtained by method of multifractal detrended fluctuation analysis the statistical criterion for accepting the hypothesis of monofractal properties of the time series is proposed. Results of investigations to identify mono- and multifractal properties of the time series of different nature are given.
Keywords: monofractal and multifractal time series; multifractal detrended fluctuation analysis; generalized Hurst exponent